Формула моей любви: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Экcмо, 2020)
Экземпляры: абонемент (20200825) / Инвентарный номер: 44946 / Цена: / Сис.шифр: 84(2Роc=Рус)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Роc=Рус)6